2022
DOI: 10.1002/pc.26800
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, thermal, and surface morphological properties of Musa acuminate peduncle fiber‐reinforced polymeric composite: Effect of alkalization and fiber loading

Abstract: This investigation focuses on studying the properties of treated and untreated Musa acuminate peduncle fiber (MAPF)‐reinforced epoxy composites. The effect of fiber weight fraction and alkali treatment on the mechanical, thermal, and morphological characteristics of MAPF‐reinforced epoxy composites was investigated for the first time. A considerable enhancement in the tensile, impact, and flexural characteristics was observed at 20 wt% fiber; beyond 20 wt%, the properties were found to decrease. The increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The lignin (L) was determined according to the TAPPI T 222 method [ 38 ]. The cellulose (C) and hemicellulose (H) content were obtained using the Kushner-Hoffer and Jaime-Wise methods [ 39 ]. Lignin, cellulose, hemicellulose, aqueous extractives (AE), and HHV for each pure raw biomass are presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The lignin (L) was determined according to the TAPPI T 222 method [ 38 ]. The cellulose (C) and hemicellulose (H) content were obtained using the Kushner-Hoffer and Jaime-Wise methods [ 39 ]. Lignin, cellulose, hemicellulose, aqueous extractives (AE), and HHV for each pure raw biomass are presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Durai et al [ 39 ] used 5% NaOH to pre‐treat Musa acuminate peduncle fibers. They observed that the tensile and flexural strength of the composites with 20 wt% treated Musa acuminate peduncle fibers increased by 4.78% and 4.84%, respectively, as compared to an untreated Musa acuminate peduncle fiber epoxy composite.…”
Section: Introductionmentioning
confidence: 99%
“…Natural fibers derived from plant materials are more eco-friendly, low-cost, renewable, and bio-compatible than petroleumbased synthetic fibers. Cellulose fiber has ample applications in the textile industry (Durai et al, 2022). During past decades, the usage of natural products has gained more attraction globally.…”
Section: Introductionmentioning
confidence: 99%